1999
DOI: 10.1021/jf990529j
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Oat (Avena sativa L.) Extracts. 1. Inhibition of Low-Density Lipoprotein Oxidation and Oxygen Radical Absorbance Capacity

Abstract: Milled oat groat pearlings, trichomes, flour, and bran were extracted with methanol and the fractions tested in vitro for antioxidant capacity against low-density lipoprotein (LDL) oxidation and R-phycoerythrin protein oxidation in the oxygen radical absorbance capacity (ORAC) assay. The oxidative reactions were generated by 2,2'-azobis(2-amidinopropane) HCl (AAPH) or Cu(2+) in the LDL assay and by AAPH or Cu(2+) + H(2)O(2) in the ORAC assay and calibrated against a Trolox standard to calculate Trolox equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 29 publications
4
58
0
Order By: Relevance
“…That was the case of the interaction between the temperature and time (AC), particle size and time (BC), and particle size and solvent (BC). ORAC results in this study (<0.001-31.10 µmol TE/g oat) were similar to reported values (2.08-28 µmol TE/g oat) from other research [6,14]. These values can be compared to ORAC contained in fruits where values range from 37.42-274 µmol TE/g [28].…”
Section: First Factorialsupporting
confidence: 89%
See 2 more Smart Citations
“…That was the case of the interaction between the temperature and time (AC), particle size and time (BC), and particle size and solvent (BC). ORAC results in this study (<0.001-31.10 µmol TE/g oat) were similar to reported values (2.08-28 µmol TE/g oat) from other research [6,14]. These values can be compared to ORAC contained in fruits where values range from 37.42-274 µmol TE/g [28].…”
Section: First Factorialsupporting
confidence: 89%
“…From this distribution it was found that 63% of the distribution was in the size of 0.50 mm. This is important since this is the size used in a great deal of reports regarding extraction of antioxidants from oat [3,8,[13][14][15][16]. Hence, the experiments proposed in this research covered this range, this to evaluate the effect of particle size in the extraction.…”
Section: Milling and Sievingmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor differences in relative activity were assigned to the reactivity preference of specific phenols towards different radical types. The correlation of activity with phenolic content is consistent with other studies 61 and it appears that most of the antioxidant activity of oats resides with the hydrophilic components and particularly the phenolic fraction in the aleurone 62 . In this study, the contribution of oat tocols accounted for , 5 % of the measured antioxidant capacity although it has been noted 60 that the assumption of equivalent reaction rates between 6-hydroxy-2,5,7,8-tetramethylchromane-2-carboxylic acid (Trolox) and tocols on which the calculation was based is not necessarily correct in all cases.…”
Section: Antioxidantssupporting
confidence: 91%
“…Among cereals, oat grain has been extensively investigated and has been shown to contain many compounds that exhibit antioxidant properties, such as tocopherols, tocotrienols, flavonoids, phenolic acids, avenantramides and sterols (Peterson, 2001). A major part of the antioxidant capacity (>95%) of oat is derived from phenolic compounds in the aleurone, and only <5% from tocols (Handelman et al, 1999). In a study on broiler chickens, partial replacement of maize with oats increased the oxidative stability of fat in meat (Lopez-Bote et al, 1998).…”
Section: Introductionmentioning
confidence: 99%